MODERN TREND OF SURGICAL TREATMENT OF BENIGN PROSTATIC HYPERPLASIA - Akilov, F.; Giyasov, Sh.; Gafarov, R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
The article is devoted to the current trend in the surgical treatment of benign prostatic hyperplasia (BPH) - various methods of endoscopic enucleation of prostate hyperplasia tissue. A brief history of formation is presented and a brief comparative analysis of the effectiveness of endoscopic techniques for prostate enucleation is carried out. The need for an adequate assessment of postoperative complications of surgical methods for the treatment of BPH and the need to develop criteria for the normal course of the postoperative period, as well as criteria for postoperative complications, was noted.